83.4k views
1 vote
Given: F(x) = 3x and G(x) = x 2 + 1 Find (F + G)(x).

3x³ + 1
 x² + 3x + 1
3x² + 1

1 Answer

2 votes

For this case we have the following functions:


f (x) = 3x\\g (x) = x ^ 2 + 1

We must find (f + g) (x). By definition of operations with functions we have to:

(f + g) (x) = f (x) + g (x)

So we have to:


(f + g) (x) = 3x + (x ^ 2 + 1)\\(f + g) (x) = x ^ 2 + 3x + 1

Answer:


(f + g) (x) = x ^ 2 + 3x + 1

Option B

User Bichanna
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.